2011
DOI: 10.1590/s1984-29612011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Metacestodes of Glossocercus auritus (Cyclophyllidea, Gryporhynchidae) in Poecilia reticulata (Pisces, Poeciliidae) from Brazil

Abstract: Studies on fish parasites in Pampulha dam, Belo Horizonte, Minas Gerais, Brazil, found specimens of Poecilia reticulata Peters, 1859 harboring natural infection by larval stages of tapeworms. A total of 250 specimens of P. reticulata were collected and analyzed between February and August 2010, of which 23 were found infected (prevalence 9.2%) with one metacestode each (mean intensity 1, mean abundance 0.09). The analyses of the parasites, particularly the morphology of rostellar hooks, made it possible to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…Its high reproduction rate and resistance to entropized environments favor its indiscriminate dispersal (Seng et al, 2008;Shafique et al, 2019;Dias et al, 2020). Although several helminth parasites have been reported in P. reticulata in Brazil (Kohn et al, 2007;Tavares-Dias et al, 2009;Pinto & Melo, 2011), infection with AFT is reported here for the first time. This poecilid species was previously reported to be infected with S. acheilognathi in Guatemala and México (Scholz, 1997;Pérez-Ponce de Léon et al, 2018).…”
mentioning
confidence: 64%
“…Its high reproduction rate and resistance to entropized environments favor its indiscriminate dispersal (Seng et al, 2008;Shafique et al, 2019;Dias et al, 2020). Although several helminth parasites have been reported in P. reticulata in Brazil (Kohn et al, 2007;Tavares-Dias et al, 2009;Pinto & Melo, 2011), infection with AFT is reported here for the first time. This poecilid species was previously reported to be infected with S. acheilognathi in Guatemala and México (Scholz, 1997;Pérez-Ponce de Léon et al, 2018).…”
mentioning
confidence: 64%
“… Australoheros facetus ( Actinopterygii : Cichlidae ); freshwater; intestine; metacestode; Pampulha Dam, Minas Gerais State; Brazil ( Pinto and Melo 2011b ).…”
Section: Parasite-host Listmentioning
confidence: 99%
“…Parvitaenia cochlearii pertenece a la familia Gryporhynchidae, parásitos de amplia distribución que infestan a varias especies de peces de agua dulce de África, Asia, Europa y América del norte. En América del sur se han registrado varios géneros (Glossocercus, Parvitaenia y Valipora) de esta familia infestando a peces colectados de ambientes naturales de Brasil (14,15,16,17); sin embargo, no existen reportes de infestaciones en sistemas piscícolas de la región.…”
Section: Introductionunclassified